Study on seismic performance of SRC special-shaped interior joints in NPP. (1st May 2021) - Xu, Zhen-Hua; Bai, Guo-Liang; Zhao, Jin-Quan; Liu, Biao
Highlights: SRC special-shaped interior joints were used in the nuclear power plant. SRC special-shaped interior joints were tested under reversed cyclic loading. The concrete damaged plasticity was considered in FEM in this work. Higher steel content can significantly improve the seismic performance of joints. The economical and effective reinforcement measures were proposed. Abstract: In order to evaluate the seismic performance of special-shaped interior joints (SSIJ) and promote the application and development of steel reinforced concrete (SRC) frame-bent structure in nuclear power plant (NPP), eight 1/4 scale SRC SSIJ were designed and manufactured. The seismic performance, failure process, failure modes and bearing capacity of SRC SSIJ were analyzed under low-cycle repeated loading test. A solid finite element model (FEM) was established through ABAQUS, which considered the plastic damage of concrete to simulate the damage evolution of the component during the actual stress process, and verified the correctness of FEM through the experimental. Furthermore, the parametric analyses on seismic behavior of SSIJ were studied, including the dislocation height of SRC beam, axial load ratio and steel content. The seismic behavior of the SRC SSIJ was significantly affected by the steel content, comparing ρ c = 3.08%, ρ b, left = 3.5% and ρ b, right = 3.08% with that steel content augments of ρ c = 5.1%, ρ b, left = 5.79% and ρ b, right = 5.18%, the corresponding ultimate load were 180.2 kN (positive) and 179.9 kN (negative), and increased by 28% and 30%, respectively. Ultimately, the economical and effective reinforcement measures were proposed, hoping to provide reference for seismic design of practical engineering application.